Ground of Model for the Generalized Criterion Forming at Differential Diagnostics of Dermatological Diseases - Bykh, A. I.; Visotska, E.; Kozina, O.; Tikhonova, A.; Porvan, A.; Zhook, A. (Information Theories & Applications, 2008)
The basic methods of decisions making in multi-criterion conditions are considered, from which the method of the weighed total for calculation of diagnostic indexes significance in differential diagnostics of dermatological diseases is chosen.
Keywords: dermatology; differential diagnostics; method of the weighed total; multi-criterion task